The future of digitalized project practices through data-savvy talent: A digital competence formation perspective - Yan Liu; Ningshuang Zeng; Eleni Papadonikolaki; Kirk Maritshane; Paul W. Chan (Project Leadership and Society (PLAS), 2024)
Amidst the disruptive backdrop of the COVID-19 pandemic, organizations are navigating toward a new normal, leveraging digital technologies to reconfigure business processes and operational practices. This study delves into the transformative effects of digitalization on project management, with a focus on integrating data-savvy talent in a data-rich era. Employing a mixed methods approach, data were collected from June to November 2022, providing a comprehensive blend of various perspectives. Quantitative and qualitative methods were adopted successively in this study to explore the formation mechanism of digital competence of talents in project management and analyze the practical experience and expectations on the impact of data-savvy talents on project management. This study highlights the crucial role of organizations in actively shaping digital competencies to align with the changing demands of project management. It also emphasizes the increasing importance of data-savvy talents, whose intrinsic understanding of digital technologies and business models is essential in transforming the project management landscape. The outcomes of this study offer both theoretical insights into the nexus of digital competence, talent management, and project management, and practical guidelines for effectively integrating new talents into project management practices.
Keywords: 650; Digital transformation; New talents; Project management professionals; Structural equation modeling; Talent management